Adaptability of rainfall simulators as a research tool on urban sealed surfaces – a review. Issue 6 (26th April 2017) - Yakubu, Mahadi Lawan; Yusop, Zulkifli
ABSTRACT: Rainfall simulators can be a useful research tool for some purposes but are quite unsuitable for others. They have been useful in soil erosion and infiltration studies for over eight decades, but the possibility of using a rainfall simulator in urban nonpoint source pollution involving urban non-erodible surfaces has not been fully explored. In this review, the versatility of different rainfall simulators of varying sizes, configurations and styles used in the past two decades are appraised for possible adaptation to urban sealed surfaces. Recommended criteria for detailed rainfall simulator reporting are also outlined.EDITOR M.C. Acreman ASSOCIATE EDITOR not assigned